2009
DOI: 10.1073/pnas.0812518106
|View full text |Cite
|
Sign up to set email alerts
|

Transient ciliogenesis involving Bardet-Biedl syndrome proteins is a fundamental characteristic of adipogenic differentiation

Abstract: Bardet-Biedl syndrome (BBS) is an inherited ciliopathy generally associated with severe obesity, but the underlying mechanism remains hypothetical and is generally proposed to be of neuroendocrine origin. In this study, we show that while the proliferating preadipocytes or mature adipocytes are nonciliated in culture, a typical primary cilium is present in differentiating preadipocytes. This transient cilium carries receptors for Wnt and Hedgehog pathways, linking this organelle to previously described regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
172
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(193 citation statements)
references
References 51 publications
14
172
1
2
Order By: Relevance
“…Inhibition of BBS10 and BBS12 induces adipogenesis and suggested that this is secondary to disruption of Wnt signalling, which could not be detected after BBS knock down. 53 Rod-cone dystrophy is thought to be a consequence of abnormal trafficking across the defective modified cilia connecting the inner and outer segments of photoreceptors leading to apoptosis. 50,54,55 Receptors for sonic hedgehog signalling are found on cilia in the developing limb buds.…”
Section: Biology Of the Diseasementioning
confidence: 99%
“…Inhibition of BBS10 and BBS12 induces adipogenesis and suggested that this is secondary to disruption of Wnt signalling, which could not be detected after BBS knock down. 53 Rod-cone dystrophy is thought to be a consequence of abnormal trafficking across the defective modified cilia connecting the inner and outer segments of photoreceptors leading to apoptosis. 50,54,55 Receptors for sonic hedgehog signalling are found on cilia in the developing limb buds.…”
Section: Biology Of the Diseasementioning
confidence: 99%
“…5L), although our data cannot discriminate between two possibilities: (1) the BBSome is constructed around the centrosome and/or basal body, or (2) the pre-assembled BBSome is recruited en bloc to the centrosome and/or basal body. We favor the former possibility, because components of the BBS-chaperonin complex, which is required for BBSome assembly (Seo et al, 2010;Zhang et al, 2012), are localized around the basal body (Marion et al, 2009). …”
Section: Construction Of the Bbsome On The Basis Of Centrosomelocalizmentioning
confidence: 99%
“…One study suggests that the receptors that initiate the WNT and HH signalling cascades reside on primary cilia transiently present on differentiating adipocytes (Marion et al, 2009). Impaired cilia formation during adipogenesis results in increased expression of the transcription factor peroxisomal proliferator-activated receptor g (PPARg), which suggests that increased adipogenesis might contribute to the obese phenotype of individuals with the inherited ciliopathy Bardet-Biedl syndrome (Marion et al, 2009).…”
Section: Signals To Differentiatementioning
confidence: 99%